Desmistificando preconceitos em relação às etnias indígenas brasileiras contemporâneas na educação em ciências do ensino fundamental : contribuições das etnociências e das tecnologias de informação e comunicação - Koeppe, Cleise Helen Botelho (2013)
Education for diversity, in a multicultural country as Brazil, is a responsability of every single individual involved in the educational process. Brazilian Indian culture has been, in this context, underestimated , full of stereotypes and prejudice. At school, quite often, it is limited to a folkloric view or reduced to native cookery singularities. Science teaching can refresh this overview by minimizing the prejudice, bringing to classroom a more selective approach, wich will consider brazilian natives and their environmental relationships. This work intend to open up the discussion on how Ethnoscience and Comunication and Information Technologies are able to help in cutting out the myths and prejudice regarding to Brazilian Indians on the last series of elementary school. The research along with pedagogical activities seeks the epistemological aspects of the construction of alterity and knowledge made by individuals, regarding to live beings, the environment and environmental education, using in this process, the Ethnoscience and remote sensing as pedagogical strategies. Writen and oral production of the individuals were gathered and studied according to Semiotics and Text Analisys. From such studies emerge three comprehensive categories wich are linked to the questions of this research. Science and technology beating prejudice and building up new social representations; ethnoscience overcoming challenges and stereotypes and placing the teaching of science in to a context, from a contemporary and polemic subject. The results show that the alterity construction is idiosyncratic, complex and progressive process, where teaching strategies can be quite helpful.